Diagnosis of autoimmune pancreatitis with cholesterol granuloma mimicking intraductal papillary-mucinous carcinoma: A case report. (2017) - Takahashi, Yusuke; Yokoyama, Naoyuki; Sato, Daisuke; Otani, Tetsuya; Mitsuma, Koko; Hashidate, Hideki
Highlights: Pancreatic cysts are often diagnosed as intraductal papillary-mucinous carcinoma. Cholesterol granuloma (CG) in the pancreas is rare. This is the first report of CG-associated autoimmune pancreatitis (AIP). AIP with CG should be considered in pancreatic cysts involving nodular lesions. This would help avoid unnecessary surgery and improve patient outcomes. Abstract: Introduction: Pancreatic cysts are often observed incidentally on abdominal computed tomography (CT). For cysts involving intracystic nodules, malignant neoplasms such as intraductal papillary-mucinous carcinoma (IPMC) should be suspected. In contrast, cholesterol granuloma (CG) rarely occurs in the pancreas, and CG-associated autoimmune pancreatitis (AIP) has not yet been reported. To our knowledge, this is the first reported case of AIP with CG mimicking IPMC. Presentation of case: A 56-year-old woman underwent abdominal CT for preoperative breast cancer screening. Asymptomatic polycystic lesions were detected in the pancreatic tail (maximum diameter, 5 cm). Magnetic resonance cholangiopancreatography and endoscopic ultrasonography revealed main pancreatic duct obstruction and a lesion with intracystic nodules (maximum diameter, 10 mm). Serum levels of pancreatic cancer tumor markers and IgG4 were within normal ranges. Because IPMC was suspected, distal pancreatectomy and splenectomy with regional lymphadenectomy were performed after surgery for breast cancer. Pathological examination of the specimen revealed no epithelial neoplasm; however, cholesterol crystals with foreign body giant cells were observed. Moreover, IgG4-positive plasma cells, diffuse lymphocyte infiltration, storiform fibrosis, and obliterative phlebitis were identified in the non-cystic pancreatic parenchyma. The final diagnosis was AIP with CG. Discussion: CG in the pancreas is rare and its pathogenesis remains unclear. The findings of the present case suggest that chronic inflammation due to AIP may cause local bleeding, and that a reaction to the leaked blood cells causes CG. Conclusions: Although preoperative diagnosis may be difficult, AIP with CG should be considered as a differential diagnosis in pancreatic cysts involving nodular lesions.